The collaborative roles of the government and private sector to foster innovation in Bahrain. Issue 1 (29th October 2019) - Modara, Marjan; Bennet, Alex; Ribiere, Vincent
Abstract : Purpose: The purpose of this paper is to explore the government and private sector collaboration by focusing on their roles in influencing the innovation activities crucial for the development of a knowledge economy (KE) in Bahrain. Design/methodology/approach: A qualitative methodology based on an explorative single multi-unit case study strategy was used with individual and focus group interviews as primary sources of data collection. Perspectives of 22 individuals and three focus groups involving participants working in private, semi-government and government sectors that influence the economy of Bahrain were collected along with reports and articles published regarding those sectors as second sources of data compilation. Findings: The preliminary findings show that Bahrain's pursuit of a KE has already begun by the government developing policies and regulations for the financial sector to innovate in financial technology (FinTech). It was also found that in order for innovation processes and products to be developed further in Bahrain, the government had to play a stronger role in promoting, facilitating and incentivizing those processes and developments. The role of the private sector emerged as the sole producer of innovation and the main entity responsible for producing innovative products and services that would inject direct values into the commercial economy of the innovation ecosystem. Originality/value: This is the first study that examines the influence of collaboration between the government and the private sector on innovation development in Bahrain. This research also provides an assessment tool that can serve as the groundwork for studies in the Gulf Cooperative Council countries since those countries share similar culture, language, religion and a hydrocarbon-dependent economy as Bahrain and are aiming to develop KE strategies.